Analysis of Tautomerism in beta-Ketobutanamides by Nuclear Magnetic Resonance: Substituent, Temperature and Solvent Effects - Laurella, Sergio Luis (2012)
Î²-ketoamides are versatile intermediates for the synthesis of several heterocycles and they are also relevant compounds in biological systems, with their tautomeric equilibria being a crucial aspect to be studied in order to understand their chemical and biological behaviour. Tautomeric equilibria of a series of Î²-ketobutanamides were analyzed by means of 1HNMR, determining that ketoamide and Z-enolamide are the main tautomeric species in solution, both presenting internal hydrogen bonds. Keto-enol equilibrium predominates over other possible tautomerisms (e.g. amide-imidol). The enol tautomer appears to be favoured by electron withdrawing substituents and non-protic solvents. Thermodynamic parameters Î”H and Î”S were determined in CDCl3 and DMSO-d6, showing that the keto-enol equilibria are exothermic and require a molecule order increase.